(untitled) (Bangladesh Journal of Medical Science, 2010)
Positive results in the treatment of low back pain with LLLT include decreased pain and improved function . LLLT has been in use and studied since the 1960s. To date, the research is still debating the effectiveness of LLLT to treat various pathological conditions A few concerns arise when examining the literature on LLLT. Many studies do not publish all their treatment parameters, which makes it difficult for the findings to be translated into clinical practice. The site of application, application method and technique, and the dosage are poorly documented. Thus, few studies meet the systemic review inclusion criteria; this limits attempts to complete meta-analyses on LLLT effectiveness. To date, very few studies have investigated the optimal wavelength, power, frequency and treatment time to obtain a therapeutic effect. Having said this, there is some evidence to suggest that LLLT decreases swelling, reduces pain and improves function. Overall the literature and research on low level laser therapy are insufficient to make conclusions on the effectiveness of laser therapy. Currently the practice of using LLLT is ahead of the evidence to support the use of the technology. This is common for most modalities used in physiotherapy and eventually the research catches up to clinical usage. Some studies may convince the therapist to use LLLT for conditions involving inflammation and for providing pain relief. DOI: 10.3329/bjms.v8i4.4709 Bangladesh Journal of Medical Sciences Vol.8(4); October 2009 pp118-128